All-in-one automated microfluidics control system. (April 2019) - Watson, Craig; Senyo, Samuel
Graphical abstract: Abstract: We present a fully-integrated solution for controlling pneumatically-driven microfluidic chips, featuring a pump, one or more pressure regulators and up to 32 solenoid valves, controlled by a microcontroller. The microfluidics control system requires only a power source and a computer or mobile device for its operation. A touchscreen interface communicates with the microcontroller over USB or Bluetooth and allows users to control the system with ease either manually or autonomously, allowing experiments to run with no user intervention. The pressure regulators were purpose-built, enabling integrated pressure sources on-board, rather than relying on external equipment. These regulators can also be used as stand-alone devices in any other application.